Pengaruh Sosialisasi, Edukasi, dan Strategi Pemasaran Produk Kopi Terhadap Loyalitas Konsumen - Laurent Regina Anjani; Muhammad Azriel Yahya; Rizcha Oktanza Fabiyola; Livia Marcella Devani; Ummu Nadhiroh Islamiah; Dona Wahyuning Laily (Community : Jurnal Pengabdian Pada Masyarakat, 2023)
Extension activities to determine the effect of socialization, education, and marketing strategies for coffee products on consumer loyalty in the framework of community service activities carried out in Puspo Village, Pasuruan Regency with the aim of helping the Rukun Sejahtera Puspo Forest Farmer Group in overcoming the problems of marketing coffee products and consumer loyalty in purchasing coffee products. Efforts that can be made in helping the Rukun Sejahtera Puspo Forest Farmer Group is to find an optimal marketing strategy to increase sales of coffee products in Puspo Village. Solutions that can be offered related to marketing strategies are by changing conventional marketing methods to more modern marketing methods, rebranding Puspo coffee products, issuing business identification numbers for Puspo farmers, conducting product promotions, and paying attention to customer satisfaction to determine how customer loyalty and the efficiency of marketing methods that have been applied.